Pengendalian Kualitas untuk Meminimalkan Jumlah Cacat pada Produk Kaleng Aeorosol - Zuraida, Rida; Rantautama, Bima; Sutrisnohadi, Notri; Pratomo, Chondro Dewo Adi (Bina Nusantara University, 2012)
2.64% is the largest defect percentage of aerosol can product of PT Multi Makmur Indah Industri. To improve the product quality, the study focused on the goal of reducing the percentage of defects using the Statistical Quality Control. After gaining control of the company, we can calculate the process capability in the aerosol can manufacture. The next step is identification of the defects causes that arise using the failure mode and effect analysis (FMEA) method to measure the defect causes risks and as an input in determining control recommendations. From the observations and data processing, it is recognized that the overall phase of the process has a process capability value above 99%. 80% of defects in the aerosol cans product occur during the process of can making, component making and printing. While the most risking defect cause is the destruction ofmachine B coating on the printing process (RPN = 245) and the quality of the welding wire on can manufacturing process (RPN = 160). Therefore, the solution to reduce the defect percentage is replacing the damaged coating machine B as well as upgrading the quality of the welding wire. Thus, it can reduce the losssale as much as 1.06% (Rp110,716,000) per month.